Analisis Yuridis Mengenai Perlindungan Hukum Penumpang Taksi Online Dalam Perspektif Kepastian Hukum Nasional Indonesia - Sahadewa Putra Nusa (PSHPM Untag Semarang, 2026)
The rapid development of online transportation services in Indonesia has raised significant legal issues regarding passenger protection. Online taxis, as part of the digital economy, provide convenience and efficiency but also pose risks such as fraud, accidents, and lack of legal certainty. This research aims to analyze the forms of legal protection for passengers of online taxis in Indonesia and formulate juridical recommendations to strengthen this protection. The study uses a normative juridical method by reviewing laws, regulations, and relevant case studies. Findings indicate that passenger protection is already guaranteed through general transportation regulations, consumer protection laws, and contractual agreements between platforms and users. However, weaknesses still exist in enforcement, dispute resolution mechanisms, and clarity of responsibilities between platforms and drivers. Legal certainty can be strengthened by harmonizing sectoral regulations, increasing government supervision, and ensuring transparent accountability. Recommendations include revising legislation to specifically regulate online transportation services, establishing clear standards of service and safety, and providing an accessible legal complaint mechanism for passengers. This study emphasizes the urgency of strengthening juridical frameworks to ensure fairness, safety, and legal certainty for passengers in the growing online transportation sector in Indonesia.